Komparasi Tafsir Mafatih Al-Ghaib dan Anwar Al Tanzil Wa Asrar Al Ta’wil tentang Musyawarah QS Ali Imran Ayat 159 - Abdul Ghoni; Asep Fathurohman; Ade Jamarudin (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
One of the most essential teachings of Islam is deliberation, because with it humans can solve all life's problems in a good and wise manner. Apart from that, in deliberations commendable qualities such as brotherhood, equality, mutual respect, not imposing their own will, understanding and acknowledging other people's views will be born even though there are differences (agree on differences). Deliberation is a negotiating activity by exchanging opinions from various parties regarding an issue to then be considered and decided and taken for the best for the common good. The term deliberation has become a public discourse among Muslim intellectuals in recent centuries, especially in the 21st century. This is due to the influence if not said to be cultural infiltration and western political theory on the Islamic world, especially in the discourse of democracy. At the time of the Prophet led the state of Medina and made deliberation one of the principles of statehood. This paper attempts to elaborate on the principle of deliberation contained in the Qur'an. Anwar al-Tanzil wa asrar. Keywords: Al-Qur'an, Interpretation, Deliberation.